Facilities for Land Rights for Investment Activities in Indonesia Based on Law Number 25 of 2007 (Analysis of Constitutional Court Decision Number 21-22/Puu-V/2007) - Bobby Kurniawan; Syafruddin Kalo; Budiman Ginting; Mahmul Siregar (PT FORMOSA CENDEKIA GLOBAL, 2022)
The need for developing countries for investment to move the wheels of their national economy is undeniable. The motive of foreign investors in investing is to seek profit. The provision of this facility is intended so that domestic investors and foreign investors want to invest in Indonesia. which is the problem with Law No. 25 of 2007 as a new investment law, is considered to provide benefits to foreign investors, especially in land rights facilities as stipulated in Article 22 of Law no. 25 of 2007, has resulted in losses for most Indonesian people. This study uses a normative juridical method. The results of the study show that as a legal consequence the acquisition of land rights (HGU, HGB and HP) as stipulated in Article 22 of Law no. 25 of 2007 must follow the applicable procedures based on the provisions for the acquisition and registration of land rights based on the provisions of Law no. 5 of 1960 concerning Basic Agrarian Regulations and their implementing regulations.